Anemia in Chronic Kidney Disease: A Cross-Sectional Study on Prevalence, Severity and Morphological Patterns in a Tertiary Care Hospital - Bhat, Waseem Hussain; Thomson, Shibi; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice)
Background: Chronic Kidney Disease (CKD) is a significant global health burden, affecting 8-16% of the population and frequently associated with anemia. The underlying causes include reduced erythropoietin production, iron deficiency and chronic inflammation. Objectives: This study aimed to determine the prevalence, severity and morphological patterns of anemia in CKD patients compared to non-CKD individuals in a tertiary care setting. Materials and Methods: A cross-sectional study was conducted over nine months (January-September 2024) at a tertiary care hospital. A total of 150 patients, comprising 60 CKD and 90 non-CKD individuals, were evaluated. Hemoglobin levels and red blood cell morphology were assessed to identify anemia prevalence, severity and patterns. Results: Anemia was observed in 90% of CKD patients, with moderate and severe anemia accounting for 50% and 25% of cases, respectively. Normocytic normochromic anemia was the most common morphological pattern, seen in 75% of CKD patients. Compared to non-CKD individuals, CKD patients were twice as likely to develop moderate or severe anemia (odds ratio: 2.0) and 1.5 times more likely to exhibit normocytic anemia (odds ratio: 1.5). Conclusion: The high prevalence and severity of anemia in CKD patients underscore the need for early identification and tailored management strategies. Further studies are warranted to confirm these findings and explore effective interventions.
Keywords: Anemia; Morphological Patterns; Chronic Kidney Disease; Cross-sectional Study; Normocytic Anemia